Dignity in a digital age making tech work for all of us - Khanna, Ro. (New York Simon & Schuster, 2022)
Rep Ro Khanna offers a revolutionary roadmap to facing America's digital divide. In Khanna's vision, "just as people can move to technology, technology can move to people. People need not be compelled to move from one place to another to reap the benefits offered by technological progress"
Includes bibliographical references and index.
Keywords: Information economy--United States